Persepsi Kemudahan dan Kebermanfaatan dalam Penggunaan Aplikasi Simpan Pinjam Online di Koperasi Karunika: Studi Pendahuluan - Sakina Nusarifa Tantri; Shine Pintor Siolemba Patiro (Universitas Bunda Mulia, 2022)
Karunika is a cooperative at Universitas Terbuka (UT) which members consists of employees of UT. In February 2021, Karunika launched an online savings and loan application (aplikasi simpan pinjam online) to make it easier for members to make savings and loans. This preliminary study aims at collecting information about perceived ease of use and perceived usefulness in affecting attitudes and interest in using “simpan pinjam online” application at the Karunika Cooperative. This study is qualitative research which collect the data through documentation, observation, and interview. Documentation is carried out to collect information from secondary sources. Observation is made by accessing the application to gain experience. Interviews were conducted with 11 members of Karunika Cooperative to obtain information about the experience of application usage. Karunika members feel the ease and usefulness of using the application due to its accessibility and subjective norms. Karunika members are encouraged to have attitudes and intentions to use the application. Socialization of the application among members of Karunika is lack because the members are spread throughout Indonesia. This causes delays in finding information from experienced members. This research is expected to give contributions to the literature about the usage of information technology in cooperative. This research can be used as the basis for system improvement in Karunika Cooperative and inspire the use of “simpan pinjam online” applications in other cooperatives. For the future research development, the result of this study is also expected to be used to formulate a research instrument to capture the broader phenomenon of using information technology.